2018
DOI: 10.1007/978-1-4939-7531-0_11
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Heteronuclear Magnetic Resonance Spectroscopy

Abstract: Magnetic Resonance Spectroscopy is a technique that has the capability of measuring metabolites in vivo and, in appropriate conditions, to infer its metabolic rates. The success of MRS depends a lot on its sensitivity, which limits the usage of X-nuclei MRS. However, technological developments and refinements in methods have made in vivo heteronuclear MRS possible in humans and in small animals. This chapter provides detailed descriptions of the main procedures needed to perform successful in vivo heteronuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Moreover, the 13 C MRS-detected increased fatty-acid metabolism is consistent with the larger astrocytic areas and mitochondrial density found in the ARC nucleus of HFD mice. 138 Interestingly, the same study reported a noticeable shift from glutamatergic to GABAergic neurotransmission on HFD animals, 125 consistent with the development of the defective control of energy homeostasis reported in HFDs. 11 Similar effects on GABAergic metabolism have been described under ketogenic diets, 137,139 where the described increase in GABAergic neurotransmission is believed to originate from the metabolism of ketone bodies to AcCoA and the concomitant decrease in the cerebral pool of oxaloacetate (OAA).…”
Section: Magnetic Resonance Imaging and Spectroscopy Of Cerebral Altesupporting
confidence: 63%
See 1 more Smart Citation
“…Moreover, the 13 C MRS-detected increased fatty-acid metabolism is consistent with the larger astrocytic areas and mitochondrial density found in the ARC nucleus of HFD mice. 138 Interestingly, the same study reported a noticeable shift from glutamatergic to GABAergic neurotransmission on HFD animals, 125 consistent with the development of the defective control of energy homeostasis reported in HFDs. 11 Similar effects on GABAergic metabolism have been described under ketogenic diets, 137,139 where the described increase in GABAergic neurotransmission is believed to originate from the metabolism of ketone bodies to AcCoA and the concomitant decrease in the cerebral pool of oxaloacetate (OAA).…”
Section: Magnetic Resonance Imaging and Spectroscopy Of Cerebral Altesupporting
confidence: 63%
“…124 Furthermore, when combined with the infusion of 13 C-labelled compounds, MRS can be used to evaluate metabolic fluxes. 125 Remarkably, in vivo and ex vivo MRS are sensitive enough to detect changes in very small structures (<9µL), such as the mouse hypothalamus. 126,127 Using 1 H MRS techniques in vivo, 22 authors investigated longitudinal changes of the hypothalamic neurochemical profile in mice fed HFD.…”
Section: Magnetic Resonance Imaging and Spectroscopy Of Cerebral Altementioning
confidence: 99%
“…Large improvements in sensitivity in animal and human studies have been achieved by detecting 13 C labeling indirectly via the J scalar coupling to bound 1 H nuclei , enhancing spatial resolution to several cm 3 at 4 Tesla as well as allowing MRSI acquisition . A detailed evaluation of the sensitivity and resolution advantages of different inverse and direct 13 C acquisition has recently been published .…”
Section: Future Prospects For 13c Mrs Studies In Humansmentioning
confidence: 99%
“…The ability to hyperpolarize 13 C labeled substrates such as pyruvate to levels 10,000x or more than the natural polarization, has generated great excitement in the MR field. While the applications in brain have been mostly focused on animal models, recent hyperpolarized data have been acquired in human brain 15. A primary limitation for studying the brain, outside of brain cancer, is due to the blood brain barrier, consisting of the capillary endothelia, which restricts the rate of [1‐ 13 C] pyruvate entry into the brain relative to other organs and makes it rate limiting .…”
Section: Future Prospects For 13c Mrs Studies In Humansmentioning
confidence: 99%
“…Non-invasive indirect carbon-13 Magnetic Resonance Spectroscopy ( 1 H-[ 13 C]-MRS) was performed as previously described 59,94 . The experimental set-up was comparable to that of 1 H-MRS, with two main differences: (1) animals underwent femoral vein cannulation for the infusion of uniformly labeled 13 C-glucose ([U- 13 C 6 ]Glc) for a scan of ~230min duration; and (2) the coil included a 13 C channel.…”
Section: Methodsmentioning
confidence: 99%